Comparison of three different target blood concentrations of propofol for induction of anaesthesia using target controlled infusion (TCI) technique - Hassan, W Mohd Nazaruddin W; Hassan, Shamsulkamarujan; Mohamad, Nik Abdullah Nik (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
We studied three different target blood concentrations (TBC) of propofol for induction of anaesthesia using target controlled infusion (TCI) technique. One hundred and thirty five ASA I and II patients, between 18-55 years of age and undergoing any type of elective surgery were included in the study. All patients were premedicated with oral midazolam 7.5 mg in the ward an hour before induction. Patients were randomly divided into three groups. Group I (n = 45) received initial TBC of 2 J,Jg/ml, group II (n = 45) TBC of 3 J.Jg/ml and group Ill (n = 45) TBC of 4 J,Jg/ml for induction of anaesthesia. Intravenous alfentanil 30 ~g/kg bolus was given as analgesia. Patients were observed for success rate of induction, induction time, effect site concentration and haemodynamic parameters at baseline, 1 minute, 3 minutes and 5 minutes after induction. Success rate of induction was 55.6 %, 86.7% and 91.1 %in group I, 11 and 111 respectively, which showed significant difference only between group I and Ill. Effect site concentration was 0.6 ~g/ml, 0.9 J,Jg/ml and 0.8 JJQ/ml in group I, II and Ill respectively which showed significant difference only between group I and II. There was no significant difference in induction time and haemodynamic parameters among the three groups. Hence, TBC 3 J,Jg/ml was comparable with TBC 4 J.Jg/ml for induction of anaesthesia using TCI technique. However TBC 2 IJQ/ml was not recommended for rapid induction.